2020
DOI: 10.1002/ped4.12176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on the expression of inflammatory factors in children with congenital heart disease undergoing intraoperative cardiopulmonary bypass: a randomized controlled trial

Abstract: Importance Dexmedetomidine inhibits the inflammatory response associated with cardiopulmonary bypass (CPB) and protects neural function. However, the mechanism of dexmedetomidine’s anti‐inflammatory pathway is unclear. Objective To investigate the effect of dexmedetomidine on the cognitive level and expression of inflammatory factors in children with congenital heart disease undergoing intraoperative CPB. Methods Ninety children with congenital heart disease were recruited and randomly divided into 3 groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“… 11 and Qiu et al . 13 also reported a similar trend, with levels of IL-6, IFN-γ, TNF-α, and NF-κB marked significantly lower in the dexmedetomidine group compared to the control at all operative and postoperative measurements,. Zhang et al .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“… 11 and Qiu et al . 13 also reported a similar trend, with levels of IL-6, IFN-γ, TNF-α, and NF-κB marked significantly lower in the dexmedetomidine group compared to the control at all operative and postoperative measurements,. Zhang et al .…”
Section: Resultssupporting
confidence: 61%
“…Many methods have been used to administer dexmedetomidine during pediatric cardiac surgery. Several studies have reported dexmedetomidine as a loading dose and as a continuous infusion during pediatric cardiac surgery 11 13 . Dexmedetomidine itself can be useful as a neuroprotective and cardioprotective agent during preconditioning, intraconditioning, and postconditioning by reducing necrosis of the cells and inhibiting oxidative stress, especially during the preconditioning period 4 .…”
Section: Discussionmentioning
confidence: 99%